(untitled) (TEST Ticontre. Theory Text Translation, 2022)
This essay analyses the perception of time in Quando. Published in Autumn 2020, the most recent work by the Portuguese poet Manuel Alegre resumes a theme dear to the author which, ever since his first writings, plays an essential role Manuel Alegre’s representation of himself and his country. In this difficult time, Quando does so even more intensely, contrasting the uprooted moment, induced by the current emergency and lockdown, with the different modes of experiencing time, from that shattered of exile to that shadowed of the present. A process in which poetry, word and music, unlocks the current time and gives back sense to that journey called life.